Rancang Bangun Alat Pembangkit Listrik Tenaga Sampah (PLTSa) Sebagai Sumber Energi Alternatif - Apriadi, Roland; Alham, Nur Rani; Muslimi; Saharudin; Manukallo, Maden Nolis Nani; Callista, Nethania; Cindyani; Zulharfian, Annisa Maharani (SainETIn : Jurnal Sains, Energi, Teknologi, dan Industri, 2024)
Garbage is waste material that can no longer be used as a result of an activity. Garbage can be used as fuel or a source for a Waste Power Plant (PLTSa). The Waste Power Plant is one of the many generators as alternative energy. The prototype of the Waste Power Plant is a small replication of the renewable energy experiment. This study uses a multimeter as a measuring instrument used to measure the resulting voltage and current. Researchers conducted research on the burning time of each type of waste and the power generated. Burning time is measured at the beginning of burning the waste until the water in the boiler boils. The current and voltage measurements are carried out with a period of the first 10 seconds to the fifth 10 seconds with different types of waste. The average power generated using paper waste is 0.07965 Watt, while the average power generated using plastic waste is 0.0580 Watt.